2018
DOI: 10.3168/jds.2018-14840
|View full text |Cite
|
Sign up to set email alerts
|

Study of the efficacy of a Streptococcus uberis mastitis vaccine against an experimental intramammary infection with a heterologous strain in dairy cows

Abstract: Streptococcus uberis is a worldwide pathogen that causes intramammary infections in dairy cattle. Nevertheless, commercial vaccines are currently not available and measures to control S. uberis mastitis are limited to the implementation of good management practices. The aim of the present study was to evaluate the efficacy of an S. uberis subunit vaccine against bovine mastitis (Laboratorios Hipra S.A., Amer, Spain) administered precalving against an experimental intramammary challenge with a heterologous S. u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Challenge of vaccinated cows with a heterologous strain of Strep. uberis showed that vaccination did not prevent infection but reduced clinical mastitis signs, bacterial count in milk, and milk yield (Collado et al, 2018). This vaccine requires the administration of 3 doses yet does not induce long-lasting immunity (https: / / www .ema .europa .eu/ documents/ product -information/ ubac -epar -product -information _en .pdf).…”
Section: Vaccinesmentioning
confidence: 99%
“…Challenge of vaccinated cows with a heterologous strain of Strep. uberis showed that vaccination did not prevent infection but reduced clinical mastitis signs, bacterial count in milk, and milk yield (Collado et al, 2018). This vaccine requires the administration of 3 doses yet does not induce long-lasting immunity (https: / / www .ema .europa .eu/ documents/ product -information/ ubac -epar -product -information _en .pdf).…”
Section: Vaccinesmentioning
confidence: 99%
“…It has been estimated that Strep. uberis is responsible for 14 to 26% of clinical mastitis cases in Canada, the United States, and the Netherlands, and it is the main cause of clinical mastitis in New Zealand and Australia (Collado et al, 2018). It has also been identified as being responsible for a large part of clinical mastitis in several European countries such as Belgium, Germany, Italy, and the UK (Bradley et al, 2007;Krömker et al, 2014).…”
mentioning
confidence: 99%
“…In several trials, the application of vaccines was able to cause a reduced severity of the clinical signs accompanied with mastitis cases caused by S. uberis and E. coli [43,44]. Furthermore, S. uberis-specific vaccines were beneficial concerning the reduction in somatic cell count and bacterial count [44]. While Schukken et al (2014) achieved a reduction in both the incidence and prevalence of intramammary infections with staphylococci [45], previous observations by Tenhagen et al (2001) were contrary.…”
Section: Discussionmentioning
confidence: 98%
“…Another possibility for avoiding the extensive use of antimicrobials could be the application of vaccines. In several trials, the application of vaccines was able to cause a reduced severity of the clinical signs accompanied with mastitis cases caused by S. uberis and E. coli [43,44]. Furthermore, S. uberis-specific vaccines were beneficial concerning the reduction in somatic cell count and bacterial count [44].…”
Section: Discussionmentioning
confidence: 99%